2019
DOI: 10.29333/iji.2019.12334a
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Organizational Stressors on Job Performance among Academic Staff

Abstract: This study investigate to test and analyse the influence of organizational stressors include role ambiguity, role conflict, and workload on job performance among academic staff. The data were collected by structured questionnaires through cluster sampling techniques and 209 academic staff from research universities inside Malaysia completed the questionnaires. Partial least squares structural equation modeling (PLS-SEM), has been employed to perform the analysis. The outcomes of Smart PLS have been assessed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 27 publications
6
17
0
Order By: Relevance
“…The results of the data analysis reinforce the assumption that work overload negates the performance of university academic staff in Malaysia, hence hypothesis 1 was supported. This present finding supports other past investigations, specifically those conducted by Yousefi and Abdullah (2019), and Teater and Mendoza (2018). To reinforce our empirical findings, we invoke the Yarkes-Dodson law (Teigen, 1994) on a stress-performance relationship, which suggests that stress causes diminishing returns in performance; after physiological or mental stimulation/stress increases performance to an optimal point, the capacity to perform gradually decreases when the intensity of stress is constant.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the data analysis reinforce the assumption that work overload negates the performance of university academic staff in Malaysia, hence hypothesis 1 was supported. This present finding supports other past investigations, specifically those conducted by Yousefi and Abdullah (2019), and Teater and Mendoza (2018). To reinforce our empirical findings, we invoke the Yarkes-Dodson law (Teigen, 1994) on a stress-performance relationship, which suggests that stress causes diminishing returns in performance; after physiological or mental stimulation/stress increases performance to an optimal point, the capacity to perform gradually decreases when the intensity of stress is constant.…”
Section: Discussionsupporting
confidence: 91%
“…In the two-way legacy process of knowledge exchange, research is the inception of lessons. Upholding this fundamental practice of research and teaching, Malaysian universities focus on the dual-core functions, namely knowledge creation and knowledge transmission (Yousefi & Abdullah, 2019). As the delivery standard of Malaysian higher education changes according to the needs of globalization, so, it goes parallel with the responsibilities of academic staff (Basarudin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…According to Jonker (2016), developed countries such as the UK, Australia and US the global changing in curriculum design and an increasing number of students especially in postgraduate positions have led to a notable demand in universities and increase job pressures of academics, as well as developing countries such as Malaysia and Indonesia. Also, the difference between types of universities could be an element that makes the difference in levels of WL, RA and RC that result in job performance directly university academic personnel, and based on the this phenomenon, it should be highlighted here that there is a major issue in research to recognize and eliminate organizational stressors that negatively influence on the academic staff performance who work in universities in Malaysia (Yousefi & Abdullah, 2019).…”
Section: Universities Performance and Stress Indicatorsmentioning
confidence: 99%
“…Henceforth, this may cause university academic personnel to encounter multitude stressors regarding their job expectations. Therefore, the three elements of the academic work which involved teaching, research and learning not only have caused complexity as it demands a deeper understanding of the nature of student learning, pressures to the relocation of the teaching and research environment around learning outcomes, and due to demand of certain courses that require a professional approach in university teaching but also, private universities at the same time play the role of competitor to public institutions Malaysia (Yousefi & Abdullah, 2019). Hence, the medium of instruction in private institutions is English while Malay language continues to be the official medium of instruction in public institutions; this difference has created some comparative advantage for students to pursue higher education in private institutions.…”
Section: Universities Performance and Stress Indicatorsmentioning
confidence: 99%
“…The second factor is Role Ambiguity. Based on research conducted by Elvina Lase (2019), role ambiguity is known to have no significant effect on employee performance, but based on research by Midya Yousefi & Abdul Abdullah (2019), it is found that role ambiguity has a significant negative effect on employee performance as well as research conducted by Arlin Adam, Andi Alim, and Dedy Maulana (2020) stated that role ambiguity is known to have a significant negative effect on employee performance.…”
Section: Introductionmentioning
confidence: 99%